Interlaboratory comparison of IDH mutation detection - Van den Bent, Martin J.; Hartmann, Christian; Preusser, Matthias; Ströbel, Thomas; Dubbink, Hendrikus J.; Kros, Johan M.; Deimling, Andreas von; Boisselier, Blandine; Sanson, Marc; Halling, Kevin C.; Diefes, Kristin L.; Aldape, Kenneth; et al. (Journal of neuro-oncology, 2013)
Isocitrate dehydrogenase (IDH) mutational testing is becoming increasingly important. For this, robust and reliable assays are needed. We tested the variation of results between six laboratories of testing for IDH mutations. Each laboratory received five unstained slides from 31 formalin-fixed paraffin-embedded (FFPE) glioma samples, and followed its own standard IDH diagnostic routine. All laboratories used immunohistochemistry (IHC) with an antibody against the most frequent IDH1 mutation (R132H) as a first step. Three laboratories then sequenced only IHC negative cases while the others sequenced all cases. Based on the overall analysis, 13 samples from 11 tumors had an R132H mutation and one tumor showed an R132G mutation. Results of IHC for IDH1 R132H mutations in all six laboratories were completely in agreement, and identified all R132H mutations. Upon sequencing the results of two laboratories deviated from those of the others. After a review of the entire diagnostic process, on repeat (blinded) testing one laboratory was completely in agreement with the overall result. A change in technique did only partially improve the results in the other laboratory. IHC for the IDH1 R132H mutation is very reliable and consistent across laboratories. IDH sequencing procedures yielded inconsistent results in 2 out of 6 laboratories. Quality assurance is pivotal before IDH testing is made part of clinical management of patients.
Gesehen am 21.02.2022